GE_GERICHTE C/22485/2017 vom 31. Mai 2018 - GE Cour de justice (2018)
DIVORCE ; MESURE PROVISIONNELLE ; VALEUR LITIGIEUSE ; OBLIGATION D'ENTRETIEN ; ENFANT ; MODIFICATION DES CIRCONSTANCES | CC.179; CPC.92.al2; CPC.296.al1; CPC.296.al3